A Feasibility study on Pavela Life-Care Community - Lagunay, Novis; Papio, Marivic; Venida, Venice (Diliman, Quezon City College of Engineering, 2002)
The population of this country is becoming older. The number of persons aged sixty and older is increasing not only because population is increasing, but also because of declining birth rates and increasing life expectancy. As such, the elderly population is a growing market potential for new business ventures. Continuing Care Retirement Communities (CCRCs) provide both housing and health care for the elderly, in addition to emphasizing social involvement and community life. A CCRC is intended to supply a continuum of care throughout the life-time of its elderly residents. It does so by maintaining an assortment of on-site medical and social service and facilities. This allows residents to enter into the community while still relatively healthy and then move on to more intensive care as it becomes necessary. In the market analysis, the need for this type of community was established based on the special needs of the elderly for more health care, the declining trend in family support for the aged due to changing family structure and increased longevity, and psychosocial needs of the elderly. The target market selected was individuals aged 35 and above, from class ABC of the population of the NCR. From the survey conducted, it was found out that the present demand for such facilities was 57.32% of the target market. Setting capacity at 200 residents, market share is estimated to be 0.062%. Appropriate marketing strategy to the target market is established, emphasizing the changing of the negative perception of Filipino people regarding retirement community and attracting them to enter and acquire the services provided. The chosen name of the community was PaVeLa Life-Care Community from the names of the pioneers of the retirement community, Papio, Venida and Lagunay. The community is to be located in the Cavite area. Pricing will be based on the contract chosen by the customer, and may either be extensive or fee-for-service. There will be four stages in marketing the retirement community: awareness campaign, pre-operations, initial operations and ongoing operations. Marketing budget for each phases are PhP 945,000; PhP 2,245,000; PhP 2,130,500; and PhP150.200 respectively. The PaVeLa is concluded to be marketable, because it shows a positive and growing demand for the facility. Knowing that there is a market for the retirement community, the technical feasibility must be determined. The production process for service industry is similar to manufacturing, such that the system takes an input and employs processes to produce necessary output. The input would be the resident's needs. And through various administrative, psychosocial and medical environments and programs, the product would be quality of life and quality of care of the resident. The PaVeLa would consist of four facilities: housing facility, community center, nursing home and a healthcare facility. A support facility will be constructed for laundry, housekeeping and maintenance. Each area must establish its capacity, manpower requirement, equipment, furniture, space requirement and layout. The results of which would be used to determine the best layout of the PaVeLa. The retirement community will accept 200 residents, 150 of which would reside on the housing facilities and the rest will occupy the nursing home. After the analysis of all specific areas, the grand layout was determined to be a one level floor for all the facilities. The site for the community is in Barangay Buenavista 1, Gen. Trias, Cavite as it satisfies the established criteria by the proponents of the project. The total investment costs is PhP 288,965,069 and the monthly operational costs amounts to PhP 3,954,331. The PaVeLa is technically feasible since the preparation and operations of the retirement community are all attainable and achievable. A project's viability relies heavily upon its financial feasibility. For most individuals, the decision to pursue a business venture is largely dependent upon the profit he will gain from it. It was estimated that the company needs Php 260 M get the project in progress. To finance the project, the company would issue Php 160 M worth of capital stock with a market value of Php 5 for the common stock and Php 6 for the preferred stock. Debt financing will also be utilized, with a loan of Php 50 M payable in 10 years from the Development Bank of the Philippines. The collateral to be used was from the land priced at Php 81 M. The financial analysis showed that the project was acceptable in all ratio tests with a 9.15% average rate of return and 5 months payback period from the beginning of the operations. The breakeven occupancy rate was determined to be 55.5% or 111 residents. From the estimated 95% occupancy, the margin of safety was computed to be 39.5%. The net present value is Php 59,852,109 and the internal rate of return is 41.827%, which is far greater than the MARR=15. With all the measures being favorable, the project is financially feasible. In the social profitability analysis, it was determined that the benefits of this project are not limited to the residents living in the community. The citizens who work within the community, the government through taxes, and the different industries that provide support equipment and infrastructure gain several advantages. Again, as evidenced by the determination of the net present worth and the internal rate of return in terms of social profitability, the project is feasible. With the project feasible in the market, technical, financial and social profitability aspects, it is therefore concluded that the establishment of PaVeLa Life-Care community in the Philippines is very much feasible!
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: Continuing Care Retirement Communities (CCRC); Retirement industry; Life care communities; Participatory monitoring and evaluation (Project management)